LT-K63 Enhances B Cell Activation and Survival Factors in Neonatal Mice That Translates Into Long-Lived Humoral Immunity - Aradottir Pind, Audur Anna; Molina Estupiñan, Jenny Lorena; Magnusdottir, Gudbjorg Julia; Del Giudice, Giuseppe; Jonsdottir, Ingileif; Bjarnarson, Stefania P. (Frontiers in Immunology, 2020)
Adjuvants enhance magnitude and duration of immune responses induced by vaccines. In this study we assessed in neonatal mice if and how the adjuvant LT-K63 given with a pneumococcal conjugate vaccine, Pnc1-TT, could affect the expression of tumor necrosis factor receptor (TNFR) superfamily members, known to be involved in the initiation and maintenance of antibody responses; B cell activating factor receptor (BAFF-R) and B cell maturation antigen (BCMA) and their ligands, BAFF and a proliferation inducing ligand (APRIL). Initially we assessed the maturation status of different B cell populations and their expression of BAFF-R and BCMA. Neonatal mice had dramatically fewer B cells than adult mice and the composition of different subsets within the B cell pool differed greatly. Proportionally newly formed B cells were most abundant, but they had diminished BAFF-R expression which could explain low proportions of marginal zone and follicular B cells observed. Limited BCMA expression was also detected in neonatal pre-plasmablasts/plasmablasts. LT-K63 enhanced vaccine-induced BAFF-R expression in splenic marginal zone, follicular and newly formed B cells, leading to increased plasmablast/plasma cells, and their enhanced expression of BCMA in spleen and bone marrow. Additionally, the induction of BAFF and APRIL expression occurred early in neonatal mice immunized with Pnc1-TT either with or without LT-K63. However BAFF+ and APRIL+ cells in spleens were maintained at a higher level in mice that received the adjuvant. Furthermore, the early increase of APRIL+ cells in bone marrow was more profound in mice immunized with vaccine and adjuvant. Finally, we assessed, for the first time in neonatal mice, accessory cells of the plasma cell niche in bone marrow and their secretion of APRIL. We found that LT-K63 enhanced the frequency and APRIL expression of eosinophils, macrophages and megakaryocytes, which likely contributed to plasma cell survival, even though APRIL+ cells showed a fast decline. All this was associated with enhanced, sustained vaccine-specific antibody-secreting cells in bone marrow and persisting vaccine-specific serum antibodies. Our study sheds light on the mechanisms behind the adjuvanticity of LT-K63 and identifies molecular pathways that should be triggered by vaccine adjuvants to induce sustained humoral immunity in early life.